Dysregulation of the JNK signaling pathway in tuberculosis: mechanisms and therapeutic strategies - Yao, Yushan; Li, Kang; Chai, Yinghui; Deng, Xianping; Li, Min; Lan, Junya; Liang, Yan; Wu, Xueqiong; Lei, Hong (Frontiers in Cellular and Infection Microbiology, 2025)
Tuberculosis (TB), which is caused by Mycobacterium tuberculosis (Mtb), remains a major infectious disease worldwide. Despite the availability of anti-TB drugs, the emergence of drug resistance, the need for prolonged treatment duration and the occurrence of side effects highlight the urgent need for new therapeutic strategies. The c-Jun N-terminal kinase (JNK) signaling pathway, which is an important member of the mitogen-activated protein kinase (MAPK) family, plays a crucial role in regulating cellular stress responses, inflammation, apoptosis, autophagy, and ferroptosis. Excessive JNK activation can induce uncontrolled inflammation, tissue damage, and chronic immune activation. In contrast, insufficient activation may impair the host’s defense, facilitating Mtb immune evasion and persistence. Such alterations disrupt the delicate immune equilibrium essential for effective pathogen clearance and host protection. This review summarizes the molecular mechanisms through which Mtb manipulates the JNK signaling pathway to disrupt host immunity, emphasizing its roles in metabolic reprogramming, apoptosis, autophagy, and ferroptosis. In addition, this review discusses potential therapeutic strategies targeting the JNK pathway, including the development of selective JNK inhibitors, with a focus on their prospects in TB treatment. Progress has been made in elucidating the role of JNK signaling pathway in TB, but further research is required to clarify its specific mechanisms and evaluate the safety and efficacy of JNK-targeted interventions. Continued exploration of this pathway may provide new targets and strategies for TB therapy.